Bile acid-binding capacity of lobster shell-derived chitin, chitosan and chitooligosaccharides. (February 2020) - Xu, Wei; Mohan, Aishwarya; Pitts, Nancy L.; Udenigwe, Chibuike; Mason, Beth
Abstract: The extraction of chitin and its derivatives, chitosan and chitooligosaccharides (COS) from lobster shell by-products and their hypocholesterolemic property through bile acid sequestration were studied. Chitin was extracted from lobster shells using chemical methods. The purity and recovery rate of extracted chitin were 96.4 and 94%, respectively, from tail shells. Chitosan was derived from chitin with a high degree of deacetylation and a molecular weight >500 kDa. Pepsin and papain were used as a combined enzymatic system for hydrolysis of chitosan, which yielded 13% COS. The enzymatically prepared COS had net positive zeta (ζ) potential of +37.6 mV, bimodal molecular weight distribution, and showed the highest bile acid-binding capacity with sodium deoxycholate at 50 mg/mL. Results indicated that COS may have different binding reactions with multiple mechanisms with the bile acids compared to chitin and chitosan. The results suggested that the lobster shell-derived chitin, chitosan and COS could be promising compounds for use in the management of hypercholesterolaemia through binding with bile acids. Highlights: Lobster shell by-products are potential sources of bioactive chitin. Relatively pure chitin was extracted from lobster shells with high recovery. Chitin, chitosan and chitooligosaccharides bound to different bile acids. The lobster shell-derived molecules could be potential agents for treating hypercholesterolaemia.